Stimulation of drawing expression to strengthen character learning - Karyono, Tri; Isa, Badrul; Masunah, Juju (Jurnal Cakrawala Pendidikan, 2025)
This study investigates the implementation of a value-based expressive drawing model within the framework of Cultural Education and National Character Building (PBKB) in elementary schools students. The objective is to explore how this model can enhance emotional intelligence and instill moral values in students through creative expression. To align with government policies, the study was conducted with 3rd graders at Cisarua 1, 2, and 3 Elementary Schools located in Bandung Barat Regency. The study examined: (i) the school’s vision and mission supporting Cultural Education and National Character Building (PBKB); (ii) the application of character education through value-based expressive drawing to enhance emotional intelligence in elementary school; (iii) the impact of this educational approach on students' values and personalities, as reflected in their learning outcomes; and (iv) changes in students’ attitudes, analyzed through children's drawings. The experimental methods aimed to improve lesson plans, teaching processes, instructional media, and the analysis of values in children's visual symbols. Results indicated positive shifts in students' attitudes and character values, as evidenced by progress reports over two semesters. Various national character traits were identified in children's expressive drawings, notably through the visualization of symbols of honesty, thereby demonstrating the effectiveness of value-based expressive drawing model in character education.